La publicidad disfrazada o el pseudoperiodismo - Castaños Martínez, Ángel J. (Estudios sobre el Mensaje Periodístico, 2007)
This text presents one of the pseudo-journalistic formats with long tradition in the print media: advertorials. It depicts how this advertising model, quite usual at the daily press, imitates, sometimes grotesquely, the forms of the editorial content and goes beyond the rules set by the Spanish law, not just in specific examples, but in its very soul. We wonder if these advertorials exceed the limits set by law when trying to avoid its differences with the editorial material or if, maybe, according to the examples of some newspapers that fight in a very tough advertising market, it is about time to brake the barrier and, accordingly, legal texts are now outdated.